2012
DOI: 10.1371/journal.pone.0050690
|View full text |Cite
|
Sign up to set email alerts
|

Side Population in Human Non-Muscle Invasive Bladder Cancer Enriches for Cancer Stem Cells That Are Maintained by MAPK Signalling

Abstract: Side population (SP) and ABC transporter expression enrich for stem cells in numerous tissues. We explored if this phenotype characterised human bladder cancer stem cells (CSCs) and attempted to identify regulatory mechanisms. Focusing on non-muscle invasive bladder cancer (NMIBC), multiple human cell lines were used to characterise SP and ABC transporter expression. In vitro and in vivo phenotypic and functional assessments of CSC behaviour were undertaken. Expression of putative CSC marker ABCG2 was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
(52 reference statements)
0
39
0
1
Order By: Relevance
“…We examined the ERK pathway and found that pERK was upregulated in our NP-siGP130-treated bladder tumors, indicating that this downstream pathway was still active and may be responsible in preventing complete abrogation of the bladder tumor. Hepburn and colleagues demonstrated that activation of the ERK pathway supported a role for cancer stem cell self-renewal and tumorigenicity (29).…”
Section: Discussionmentioning
confidence: 99%
“…We examined the ERK pathway and found that pERK was upregulated in our NP-siGP130-treated bladder tumors, indicating that this downstream pathway was still active and may be responsible in preventing complete abrogation of the bladder tumor. Hepburn and colleagues demonstrated that activation of the ERK pathway supported a role for cancer stem cell self-renewal and tumorigenicity (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on recurrence in CSCs, a small subpopulation of tumor cells that are tumor‐initiating and drive the production of cancer cells. Progress in this field has highlighted the necessity of targeting these cells as they strongly determine the response to treatment [25]. An important relationship between c‐MYB and CSCs was recently reported, with important implications for breast cancer cell invasion and metastasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is linked to MAPK signaling, since activity of that pathway has previously been shown to be required for transforming growth factor beta (TGFβ)-induced EMT and is associated with invasiveness of urothelial carcinoma cells[43], [44]. Moreover, high MAPK activity has been linked to the maintenance of bladder cancer stem cell characteristics[45].…”
Section: Discussionmentioning
confidence: 99%